The impact of binaural beats on creativity - Reedijk, Susan A.; Bolders, Anne; Hommel, Bernhard (Frontiers in Human Neuroscience, 2013)
Human creativity relies on a multitude of cognitive processes, some of which are influenced by the neurotransmitter dopamine. This suggests that creativity could be enhanced by interventions that either modulate the production or transmission of dopamine directly, or affect dopamine-driven processes. In the current study we hypothesized that creativity can be influenced by means of binaural beats, an auditory illusion that is considered a form of cognitive entrainment that operates through stimulating neuronal phase locking. We aimed to investigate whether binaural beats affect creative performance at all, whether they affect divergent thinking, convergent thinking, or both, and whether possible effects may be mediated by the individual striatal dopamine level. Binaural beats were presented at alpha and gamma frequency. Participants completed a divergent and a convergent thinking task to assess two important functions of creativity, and filled out the Positive And Negative Affect Scale – mood State questionnaire (PANAS-S) and affect grid to measure current mood. Dopamine levels in the striatum were estimated using spontaneous eye blink rates (EBRs). Results showed that binaural beats, regardless of the presented frequency, can affect divergent but not convergent thinking. Individuals with low EBRs mostly benefitted from alpha binaural beat stimulation, while individuals with high EBR were unaffected or even impaired by both alpha and gamma binaural beats. This suggests that binaural beats, and possibly other forms of cognitive entrainment, are not suited for a one-size-fits-all approach, and that individual cognitive-control systems need to be taken into account when studying cognitive enhancement methods.